Effect of poplar-type propolis on oxidative stability and rheological properties of O/W emulsions - EL-GEUNDOUZ, Soukaina (2019)
Propolis is known to possess antioxidant activity. However, there is no information on this activity in emulsions O/W. The protective effect of propolis on the oxidation and rheological properties of emulsions O/W containing wheat germ and almond oils was evaluated. Emulsions O/W were prepared with different concentration of propolis extract, almond oil and wheat germ oil. All emulsions physically stable without phase separation were stored at 37 °C for 9 weeks. Chemical composition of propolis was established by Gas chromatography coupled to mass spectrometry. Rheological characterization of different emulsions was performed evaluating consistency index and flow behavior index. The oxidation was monitored by measuring the lipid hydroperoxides and thiobarbituric acid-reactive substances (TBARS) methods. Flavonoids, phenolic acid esters, and aromatic acids were the main groups of compounds found in propolis. The results showed that popolis was good antioxidant in the concentration of 0.02 and 0.04% when lipid phase was constituted by almond oil. The rheological behavior is typical of a non-Newtonian fluid, being almond oil more adequate for having a higher stable O/W emulsion.